Actividad física y bienestar en un contexto de pandemia por COVID-19 - González Insua, Francisco (2024)
Preventive measures of social isolation implemented in response to the COVID-19 pandemic have led to decreased levels of physical activity and well-being. This study (n = 308) analyzed the relationship between weekly energy expenditure levels (METs; International Physical Activity Questionnaire, IPAQ) and well-being (Pemberton Happiness Index, PHI). The physical space where the action was performed and the person/s with whom it was done moderate the positive relationship between physical activity levels and well-being. Individuals who were active outdoors and did physical activity with others reported greater well-being. The findings highlight the importance of engaging in physical activity in natural spaces and with other people. This is especially important in pandemic contexts, where people are often isolated from others.